2019
DOI: 10.1021/acs.jmedchem.9b01666
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen Possibilities To Investigate the Regulation of Polyamine Metabolism Revealed by Novel C-Methylated Spermine Derivatives

Abstract: The biogenic polyamines, spermine (Spm) and spermidine, are organic polycations present in millimolar concentrations in all eukaryotic cells participating in the regulation of vital cellular functions including proliferation and differentiation. The design and biochemical evaluation of polyamine analogues are cornerstones of polyamine research. Here we synthesized and studied novel C-methylated Spm analogues: 2,11-dimethylspermine (2,11-Me2Spm), 3,10-dimethylspermine (3,10-Me2Spm), 2-methylspermine, and 2,2-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Additionally, 1,12-Me 2 SPM may serve as a lead compound for the design of related molecules with improved safety profiles. In particular, recent analyses of structurally similar compounds have indicated that positioning of the methyl groups of these compounds alters their biochemical properties with regard to polyamine metabolic (38). Thus, the results reported in this study provide proof of principle that dimethylated SPM mimetics are effective in decreasing SPD levels in SRS-affected cells as well as in multiple tissues in vivo, paving the way for further discovery and development in the understanding and treatment of SRS.…”
Section: Dimethylspermine Reduces Spermidine Accumulation In Srssupporting
confidence: 59%
“…Additionally, 1,12-Me 2 SPM may serve as a lead compound for the design of related molecules with improved safety profiles. In particular, recent analyses of structurally similar compounds have indicated that positioning of the methyl groups of these compounds alters their biochemical properties with regard to polyamine metabolic (38). Thus, the results reported in this study provide proof of principle that dimethylated SPM mimetics are effective in decreasing SPD levels in SRS-affected cells as well as in multiple tissues in vivo, paving the way for further discovery and development in the understanding and treatment of SRS.…”
Section: Dimethylspermine Reduces Spermidine Accumulation In Srssupporting
confidence: 59%
“…The ability of racemic 1,12-Me2Spm, 2,11-Me2Spm and 3,10-Me2Spm ( Fig. 2B ) to serve as substrates for SMOX decreased as the methyl group was positioned closer to the secondary (N4) amino group, and for 3,10-Me2Spm, kinetic parameters were impossible to determine [ 19 ]. This is likely because the methyl group at the third position of the Spm backbone may restrict the proton splitting at the C3 carbon atom and influence the formation of the Shiff base, a key intermediate of the SMOX reaction.…”
Section: Resultsmentioning
confidence: 99%
“…2B ) towards SMOX and PAOX. Rac -2,11-Me2Spm was a comparatively poor substrate of SMOX, having a Vmax of 124 pmol/min/μg protein and a Km of 121 μM, while the activity of PAOX was inhibited for 60% only at the 500 μM concentration, when a fixed 50 μM concentration of the substrate N 1-Ac-Spd was used in the PAOX assay [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mutant and genetically modified microorganisms and cell lines, as well as transgenic animals have been widely used for these purposes during the last decades [7]. However, there is still a need for specific inhibitors and inducers of the key enzymes of polyamine metabolism, as well as functionally active mimetics of Spm and Spd [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%